PERANAN WAKAF PRODUKTIF PEMUDA MUHAMMADIYAH UNTUK KESEJAHTERAAN WARGA DESA LONGKEYANG, BODEH, PEMALANG - Amirul Bahri (Indonesian Journal of Islamic Literature and Muslim Society, 2016)
This study aims to examine the role of productive endowments Muhammadiyah Youth in Longkeyang, Bodeh, Pemalang. As for the issue being studied is how the first step and productive management of waqf movement Muhammadiyah Youth in Longkeyang? In addition, it will also examine how far the role of Muhammadiyah youth in productive endowments Longkeyang for the welfare of citizens. The results of this study, among others, the initial step of productive endowments movement Muhammadiyah Youth in Longkeyang namely, the anxiety of citizens and Muhammadiyah youth with a stagnant organization, so no worries "if Muhammadiyah in Longkeyang soon going to run out". Then the Working Body Shaping Development Branch of Muhammadiyah (BP2RM) and Gerakan Desa Wakaf Longkeyang coins For Productive Waqf. Meanwhile, the management of waqf productive Muhammadiyah Youth in Longkeyang the coins collected from endowments then bought land 1,500 m and maximized as initial capital. Then, the donated land is managed jointly. Meanwhile, the role of productive endowments Muhammadiyah youth for the welfare of citizens in Longkeyang could be felt, especially on the management of waqf land and also from intercropping banana crops. In addition, some programs that have resulted from the productive management of waqf endowments shroud and fund education in schools for cadres of Muhammadiyah.